Impact of citizen control on regulatory compliance with standard transparency portals in sanitation companies in southern Peru - Calderón Paniagua, Dennys Geovanni (2021)
The main objective of the research was to analyze the impact of citizen control on the regulatory compliance of standard transparency portals (PTE) of sanitation companies in southern Peru. Regarding the type of research, this work is framed in the basic type, on the research design, it was descriptive level, since it has the purpose of generating new knowledge by evaluating the impact that is generated in the level of compliance with the norms applicable in the PTEs of the sanitation companies of the regions located in the south of Peru through the application of citizen control, within the legal norms of access to public information and social control, strengthening citizen participation. The population and sample consisted of the 4 sanitation companies located in the southern regions of the Peruvian territory, specifically in the regions of Arequipa, Moquegua, and Tacna. A registry analysis was also used. It is concluded that the impact generated after the application of citizen control in the verification of the level of regulatory compliance of the PTE in the sanitation companies of southern Peru was a compliance percentage of 30.5 % categorized with the qualification of “They need to improve”, this result shows the low level of regulatory compliance and demonstrates the deficient transparency of public information that these companies have towards the population.